Hubungan Kinerja Keuangan dengan Harga Sahani pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Periode Tahun 2007-2009 dengan Pendekatan Altman Z Score - Kartini Kartini; Reza Widhar Pahlevi (Jurnal Aplikasi Bisnis, 2017)
This empirical study intended to determine the relationship between financial performance with stock prices at the manufacturing company listed on the Indonesia Stock Exchange-year period 2007-2009 with the approach Altman Z Score.The population in this study are all listed manufac uringcompanies (listing) in Indonesia Stock Exchange during the years 2007 to 2009 (446 samples). The data was drawn from the Indonesia Stock Exchange ("Pojok BEI UII") and the book Indonesia Capital Market Directoiy (ICMD). This research includes two variables: financial performance and stock prices. Chi square test was used toanalyze the relationship between Z scores with stock prices. The result of chi square analysis indicated that there was a significant relationship between financial perfotmance in the stock price approaches Altman method (Z score value). It could be concluded that the higher a company's financial performance, the Higher business profits and the more benefits that can be enjoyed by theshareholders as well as themore likely thestock price increases. Vice versa if the lower a company's financial performance, the lower income and less profit business that can be enjoyed by the shareholders and also the less likely the company's stock price increases.